Chok-Anan aroma analysis: Descriptive analysis of volatiles from selected tropical plants - Sunanta, Piyachat; Sriwichai, Trid; Tangpao, Tibet; Sommano, Sarana R (Journal of Postharvest Technology, 2016)
The present report describes the Descriptive Analysis (DA) of aromatic profile of some tropical plants. The standard selection criteria of the panellists was performed and preference was made to those who were familiar with tropical aromatic plants. The specific descriptive terms were by consensus among the panellists together with the analysed descriptors derived from the volatile compositions from Gas Chromatography coupled with mass spectrometry (GCMS) results. Here, we presented lists of the descriptive terms used to analyse the aromas from fresh or extract of basils, garlic, some species of the Zanthoxylum and rhizomes of the ginger family. In the context of testing this protocol, we performed the descriptive analysis of fresh and heated Chok-Anan mango purée. Six aromatic terms were (viz., mango identity, tropical fruit, fermented, green, sour fruit and sweet) generate by the panellists which were referred to the GCMS results. Panellists rated the intensity (scaling from 0 - 15) of the aromas. The results illustrate that green tropical fruit and mango identity were dominant in Chok-Anan mango purée. Heat treatment increased the intensity of the described mango aromas.